Nutritional Status and Food Consumption of Buddhist Monks in Mueang District, Khon Kaen Province - Phachan, Sarawin; Muktabhant, Benja (Srinagarind Medical Journal, 2016)
Background and objectives: Nutritional status and food consumption of Thai Buddhist monks are related to non-communicable diseases. This study was aimed to investigate the nutritional status and food consumption of Buddhist monks in Mueang district, Khon Kaen province. Methods: The cross-sectional descriptive study of 184 Buddhist monks from 40 temples were selected by systematic random sampling. Food consumption data were collected using 24-hr dietary recall and food frequency questionnaires. The energy and nutrient intakes were calculated by INMUCAL version 3. The nutritional status was determined by body mass index (BMI) and waist circumference (WC). Results: About half of the studied monks (46.2%) were in the 36-59 year-old group, and 53.8% went into priesthood in the range of 1-5 years. While 11.4% of the monks were found to be underweight (BMI <18.5 kg/m2), 50% either overweight or obese (BMI ≥ 23 kg/m2), and 27% had abdominal obesity (WC ≥ 90 cm). Sticky rice was their staple food, fish, and vegetable were eaten everyday by 73.4%, 66.9% and 88.0%, respectively. Fried or stir fried food were consumed daily by 53.3%. Favourite drinks such as ovaltine, tea and coffee were consumed daily by 54.9%. Energy and protein intake were 54.5%, 81.7% of Thai recommended daily allowance. The multiple logistic regression analysis showed that the consumption of desserts was correlated with the status of being overweight or obese (ORadj = 2.45, 95%CI = 1.15 – 5.24). Conclusion: Overnutrition was evident in half of the Buddhist monks and this was found to be associated with eating desserts. Buddhist monks and lay people need health education about the consumption of healthy foods.